The Holy and Great Council of the Orthodox Church and Interreligious Dialogue - Tsompanidēs, Stylianos Ch. (The ecumenical review, 2020)
This article examines how, through a pan-Orthodox synodical decision, the Orthodox Church has for the first time officially asserted its obligation to enter into dialogue with people of other cultures and religious beliefs and emphasized the value of serious and clear interreligious dialogue to promote mutual trust, peace, and reconciliation. The Holy and Great Council of the Orthodox Church of Crete clarified that interreligious dialogue excludes both syncretism and proselytism, and that interreligious dialogue needs to be accompanied by the condemnation of fundamentalism, nationalism, and the religious justification of violence. Finally, this article makes reference to the basic principles of the Orthodox tradition regarding the promotion of interreligious dialogue and emphasizes that dialogue entails respect for other religions but also discernment.